The Welfare Level of Rubber Farmers During the Covid-19 Pandemic (Case Study in Bathin II Babeko District Bungo Regency) - Isyaturriyadhah Isyaturriyadhah; Kris Mahyudi; Asminar Asminar (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2024)
The COVID-19 pandemic has significantly impacted the agricultural sector, especially the welfare of rubber farmers who depend on production and market access. Supply chain disruptions, falling commodity prices, and mobility restrictions are the main challenges faced by farmers. This study aims to determine the welfare level of rubber farmers during the COVID-19 pandemic with a case study in Suka Makmur Village, Bathin II Babeko District, Bungo Regency, Jambi Province. The research was conducted from February 15 to March 15, 2021. The research location was chosen purposively because it has the region's highest level of rubber production. The population in this study was 400 rubber farmers, and the number of respondents was as much as 10% or 40 people, as determined by random sampling. The data used consisted of primary data obtained through interviews using questionnaires and secondary data obtained from relevant agencies. This study used a quantitative descriptive approach to analyze eight variables of welfare indicators according to the Central Bureau of Statistics: population, health and nutrition, education, employment, consumption levels and patterns, environment, poverty, and social. The analysis used a Likert scale to measure respondents' perceptions of each indicator. The results showed that all indicators were in the high category, with an overall mean value of 177.975. This shows that, in general, rubber farmers in Suka Makmur Village were able to survive socioeconomically during the pandemic. These results provide an empirical picture of the dynamics of farmer welfare amid a global crisis that can be used as a reference in formulating policies for the protection and empowerment of farmers in the future